Porn Studies - Williams, Linda, 1946- (Book collections on Project MUSE., 2004)
'Porn Studies' offers a cultural study of pornographic film & video, acknowledging that with a generated revenue greater than that of American football, basketball & baseball combined, pornography has assumed a central role in contemporary American popular culture.